Teorema de Pitágoras: aplicações em objetos de aprendizagem - Balbino Júnior, Valci Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research studies the famous Pythagorean theorem, including some demonstrations, applications and the development of a learning object. The main purpose of this learning object is to help students from basic education with the geometric comprehension of the theorem in a ludic way. The part of the theory of the angles geometry necessary to the understanding of this study will be presented, so the demonstrations can be better understood. This work will be divided in four parts: A brief history; Geometric Concepts; Pythagorean Theorem; Learning Objects. A brief history presents the philosophical, cultural and historical aspects that in uenced many civilizations as a result of the theorem. Geometric Concepts is about the properties and the basic concepts of the geometry, especially the triangle geometry, which is essential to the development unleashed by the theory. Pythagorean Theorem presents demonstrations and results of the theorem or that are resulting from it. Learning Object covers the theoretical and practical aspects in the development of a learning object created in Flash

Este trabalho realiza um estudo sobre o famoso Teorema de Pitágoras, abrangendo algumas demonstrações, aplicações e o desenvolvimento de um objeto de aprendizagem, cujo objetivo é auxiliar, de modo lúdico, na compreensão geométrica do Teorema no ensino básico. Para que as demonstrações sejam melhor compreendidas, será apresentada a parte da teoria da geometria dos triângulos necessária para o entendimento do estudo em questão. Assim, este trabalho será dividido em quatro partes: Um breve histórico; Conceitos de Geometria; Teorema de Pitágoras; Objetos de Aprendizagem. Um breve histórico: apresenta os aspectos losó cos, culturais e históricos que in uenciaram diversas civilizações em decorrência do teorema. Conceitos de Geometria: trata de propriedades e conceitos básicos da geometria, em especial a geometria dos triângulos, essenciais no desenvolvimento desencadeado pela teoria. Teorema de Pitágoras: apresenta demonstrações e resultados do teorema, ou em decorrência deste. Objeto de Aprendizagem: abrange aspectos teóricos e práticos na elaboração de um Objeto de Aprendizagem escrito em Flash
Keywords: Geometry; Geometria; Matemática - Estudo e ensino; Pitagoras, Teorema de; Aprendizagem